(P square - 2pq + q square) - r square × s square
Answers
Answered by
5
Question:-
(P square - 2pq + q square) - r square × s square
P^2q - pr^2 - pq + r^2
=P × (pq-r^2)-(pq- r^2)
=(Pq-r^2) × (p-1).......
hope it helps you..
Answered by
74
Answer:
(P square - 2pq + q square) - r square × s square
P^2q - pr^2 - pq + r^2
=P × (pq-r^2)-(pq- r^2)
=(Pq-r^2) × (p-1).......
Step-by-step explanation:
Similar questions
Environmental Sciences,
6 months ago
Math,
6 months ago
Physics,
1 year ago
Science,
1 year ago
Math,
1 year ago